Assessing the generation, recycling and disposal practices of electronic/electrical-waste (E-Waste) from major cities in Pakistan. (1st February 2019) - Sajid, Muhammad; Syed, Jabir Hussain; Iqbal, Mehreen; Abbas, Zaigham; Hussain, Imran; Baig, Muhammad Anwar
Highlights: Quantification of e-waste inventory and its processing discussed from Pakistan. Local generation of e-waste in Pakistan is calculated about 38 kt per year. The study reveals that 50 kt of e-waste is being imported as scrap to Pakistan. This study recommends need for effective monitoring & control of informal e-waste. Abstract: Rapid increase in the quantity of electronic/electrical-waste (e-waste) has become an emerging issue throughout the world. To avoid higher expenditures on safe disposal and recycling, large quantities of e-waste are being exported from developed to developing countries like Pakistan. Emerging issue of e-waste in Pakistan demands its effective management strategy for the country. However, it cannot be achieved until assessment of e-waste quantification and disposal is carried out. The main objective of this study was to quantify the e-waste inventory and it's processing from major cities of Pakistan to evaluate its generation (domestic/import) and recycling practices. This study comprises the information of only those e-waste items (desktop computers, laptops/notebooks, computer monitors and liquid-crystal display units) which form the major portion of e-waste imported to Pakistan. Survey based data collected from three major cities/areas have been extrapolated to develop an e-waste generation inventory for the country. The study reveals that approximately 50 kt of e-waste is being imported as scrap in addition to its local generation of about 38 kt per year. During field visits and data collection surveys, it has been observed that the processing of e-waste in the country is being carried out in crude manner without safety gears. Findings of our study strongly recommend dire need for urgent and effective monitoring as well as control of informal e-waste management in Pakistan.